Service Quality of Mueang Ubon Ratchathani Agricultural Co-operatives - อ่อนนุ่ม, นิรันดร์; จึงสุวดี, กิตติมา; คำผา, ประนอม (RMUTT Global Business and Economics Review, 2014)
The research aimed to study the service quality of Mueang Ubon Ratchathani Agricultural Co-operative as perceived by its members classified by age, sex, income, education and membership duration. The population in the research was 5,943 members of Mueang Ubon Ratchathani Agricultural Co-operative. The samples were determined by using Krejcie and Morgan’s table and a total of 361 samples were derived by a proportionate stratified random sampling. The research instrument was a five-rating scale questionnaire with a confidence value equivalent to .97 Statistics used in data analysis were percentage, mean, standard deviation, t-test and F-test. The research findings were as follows. The service quality of Mueang Ubon Ratchathani Agricultural Co-operative was at a high level as given in a descending order: attention to give service, reliability, confidence of the service users, concrete service and response of the service users. The samples who were different in sex held no different opinion towards the service quality of Mueang Ubon Ratchathani Agricultural Co-operatives. The samples that were different in age, income, education,membership duration held different opinions towards the service quality of the organization under study. Keywords:Service quality, Mueang Ubon Ratchathani Agricultural Co-operatives, service care, reliability, confidence of the service receivers, concrete service, and response of the service users.